Analisis Peran Pendidikan Karakter dalam Project Penguatan Profil Pelajar Pancasila pada Peserta Didik Kelas IV di SD Negeri Bibisluhur 1 Surakarta - Sarafuddin Sarafuddin; Muhammad Faruq Hanafi; Ratih Trisna Dewi (Lembaga Pengembangan Kinerja Dosen, 2026)
The idea of directly observing how character education plays a role in strengthening the Pancasila Student Profile project thru an analytical approach. The concrete form of these steps will be seen in the process of character formation for students based on the Pancasila Student Profile project at the elementary school level. This research aims to clearly understand thru an analytical approach: (1) The role of character education in strengthening the dimensions of the Pancasila student profile thru project-based learning at SD Negeri Bibisluhur 1 Surakarta, (2) The challenges faced by teachers in implementing character education in project-based learning to strengthen the Pancasila student profile at SD Negeri Bibisluhur 1 Surakarta, and (3) The opportunities that can be utilized to optimize character education in project-based learning to strengthen the Pancasila student profile at SD Negeri Bibisluhur 1 Surakarta. This research uses a qualitative approach with a case study at the elementary school level. The research findings indicate that character education makes a significant contribution to developing students' attitudes and behaviors that reflect Pancasila values, such as mutual cooperation, justice, and respect for differences. Thru project-based learning activities, students are not only encouraged to understand these values but also to apply them in their daily lives. The conclusion of this research is that character education serves as a foundation supporting the successful implementation of the Pancasila Student Profile project, which in turn can strengthen national character development from an early age in the elementary school environment.